The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1136/bcr-2015-210866
|View full text |Cite
|
Sign up to set email alerts
|

Use of steroids for management of varicella pneumonia

Abstract: Varicella pneumonia (VP) is a critical complication of varicella infection and still carries significant morbidity and mortality, often requiring intensive care unit admission. Current accepted treatment is with intravenous aciclovir and organ support, if required. We report two cases of VP with acute respiratory failure, successfully treated with intravenous steroids in addition to aciclovir. Further research into the benefits of steroid therapy in VP is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Treatment for patients presenting with Varicella pneumonia would be to begin IV acyclovir with intensive supportive care [ 15 , 16 ]. The use of steroids as part of the treatment regimen remains controversial, yet a multitude of case reports have included steroids as part of care management [ 17 , 18 ]. Treatments using Varicella IG (VZIG) have been recorded as treatment or prophylaxis, but in most cases, the use of immunoglobulins is time-sensitive with efficacy decreasing as the disease progresses [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for patients presenting with Varicella pneumonia would be to begin IV acyclovir with intensive supportive care [ 15 , 16 ]. The use of steroids as part of the treatment regimen remains controversial, yet a multitude of case reports have included steroids as part of care management [ 17 , 18 ]. Treatments using Varicella IG (VZIG) have been recorded as treatment or prophylaxis, but in most cases, the use of immunoglobulins is time-sensitive with efficacy decreasing as the disease progresses [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of corticosteroid is still debated and is thought to alter the uncontrolled immune host response to the virus by inhibiting T cells function and neutrophil adherence to epithelial cells [16] . Some studies showed clinical improvement, but some mentioned at risk of superinfections [16,17,18,19] . Reports showed that use of steroids prior varicella infection might cause fulminant hepatitis [12,13] .…”
Section: Radiologic Chest X-ray Features Of Varicellamentioning
confidence: 99%
“…Reports showed that use of steroids prior varicella infection might cause fulminant hepatitis [12,13] . Nevertheless, the use of steroids remains a clinical decision [19] . Our decision to add another antibiotic and stop the steroid was based on clinical judgment regarding the occurrence of bacterial superinfection.…”
Section: Radiologic Chest X-ray Features Of Varicellamentioning
confidence: 99%